Aggregate Module System of Geoinformation Support for Volcanic Risk Management - Oleg I. SHEVCHUK; Valery M. ABRAMOV; Igor A. SIKAREV; Oksana PETRIEVA; Eugene P. ISTOMIN; Vyacheslav G. BURLOV; Ekaterina M. KORINETS; Mikhail B. SHILIN; Yaroslav A. PETROV; Tatiana V. VEKSHINA (Communications of International Proceedings, 2021)
Considered development results of geoinformation support system for volcanic risk management within environmental economics. In research, there are used risk management approach, web technologies and building database methods in distributed networks. As research result, it is proposed the using of remote sensing and modelling data to increase the efficiency and reliability of volcanic risk management within environmental economics. As digital geoinformation support instruments, it is proposed to use aggregate modular geoinformation support systems, which integrate heterogeneous hardware and software resources with the use of web-technologies in distributed networks. As study results, demonstrated examples for Cumbre Vieja 2021 eruption. The presented in article research results have significant scientific novelty and can be useful for different stakeholders in volcanic risk management area. For data exchange and discussion during the study, platform https://www.researchgate.net/profile/Valery_Abramov2/ was used.
Keywords: Volcanic Risk Management; Geoinformation Support; Environmental Economics